PENINGKATAN PERTUMBUHAN DAN EFISIENSI PAKAN IKAN GABUS (Channa sriata) MELALUI OPTIMASI KANDUNGAN PROTEIN DALAM PAKAN - Yulisman Yulisman; Mirna Fitrani; Dade Jubaedah (Fakultas Perikanan dan Kelautan, Universitas Riau, 2012)
An experiment was conducted to investigate the effect of protein levelin diet on feed eficiency and growth rate of Snakehead (Channa striata). Fivediet with different level of protein, diet P25(25% protein); P30 (30% protein); P35(35% protein); P40 (40% protein); and P45 (45% protein) were applied in thisexperiment. Ten fishes with initial body weight range 0.7 – 1.0 gram were rearedin each aquarium (water volume 10 L). Fishes were fed three time a day, atsatiation. Fish reared for 30 days.The result showed that growth rate and feedefficiency of fish fed diet 25% protein level (P25) were0.28 g and 2.46%, diet30% protein (P30) were 0.71 g and 9.86%, diet 35% (P35%) were 0.84 g and14.18%, diet 40% protein were 1.17 g and 16.97%, or diet 45% protein (P45)were 1.00 g and 9.58%. Based on BNT test showed that diet 40% protein levelwas higher growth rate and feed efficiency of fish than others diet. While survivalrate of fish fed diet 25% protein level was 50%, diet 30% protein was 46.67%,diet 35% protein was 76.67%, diet 40% protein was 63.33%, or diet 45% proteinwas 100%. Based on analysis of varians, had no significant different on survivalrate.Water quality of rearing media were temperature range was 26 – 29oC, pHwas 6.7 – 7.2, dissolved oxygen was 1.46 – 4.16 mg.L-1, and ammonia was 0.014- 0.182 mg.L-1.Keywords : Protein level in diet, feed efficiency, growth rate, Channa striata